Theoretical aspects of molecular recognition - Harmat, Veronika (Array, 2009)
Summary: Molecular recognition is a key process in non-covalent interactions, which determines, among others, host-guest complexation, drug action and protein-protein interaction. A simple and attractive formulation is the lock-and-key analogy defining the host as a lock accommodating the guest as a key. We stress three major aspects of molecular recognition, determining both complementarity between host and guest and similarity within a group of guest molecules. These aspects are: steric, i.e. maximization of close contacts, electrostatic, i.e. maximization of electrostatic attraction between host and guest, as well as hydrophobic, i.e. avoiding hydrophobic hydration, which can be reached by the maximization of apolar contacts between interacting molecules. Some examples are presented from our laboratory: the complexes of acylaminoacyl peptidase with small peptides, the effect of heparin binding on inhibitory potency of C1-inhibitor as well as small-molecule ligand binding to prolyl oligopeptidase and calmodulin